Influence of providing information to participants about development of trial outcomes on response rates and attitudes to questionnaire completion: Protocol for a study within a trial [version 2; peer review: 2 approved]. - Hayes, Catherine (My University, 2019)
Background: Issues with questionnaire completion introduce bias and limit examinations in trials. Improving communication with participants about trial processes, such as outcome and questionnaire development, may improve questionnaire completion and response rates. Providing information about the involvement of stakeholders in the development of core outcome sets (COS) measured in trials may improve responding by tapping into subjective norms and behaviour change mechanisms. The aim of this Study Within a Trial (SWAT) is to examine if questionnaire response rates and participants’ attitudes towards questionnaire completion are impacted by providing information about COS use in a trial of a complex intervention. Methods: This is a randomised, single-blinded, parallel group intervention SWAT, embedded within a feasibility trial of an infant feeding intervention to prevent childhood obesity. The SWAT intervention consists of a brief written description and explanation about the development and use of a COS of infant feeding outcomes to prevent childhood obesity, used in the trial. Participants are parents or caregivers of infants aged two months at questionnaire completion. Participants will be randomly assigned to receive the SWAT intervention prior to questionnaire completion (SWAT Intervention), or not (SWAT Comparator). The primary outcome of interest is response rates, which will be measured as proportion of questionnaire completion and individual item response rates. Participants’ attitudes will also be assessed using closed-ended and an open-ended question to evaluate participants’ attitudes about questionnaire completion. Discussion: We hypothesise that providing information about development and use of a COS will increase questionnaire response rates and attitudes toward questionnaire completion relative to the control condition. Findings will indicate the potential usefulness of this strategy for improving participant attitudes and response rates in trials. Trial Registration: This SWAT is registered on the Northern Ireland Hub for Trials Methodology: Research SWAT Repository ( SWAT57).
PUBLISHED
Keywords: Core outcome set; COS; Study within a trial; SWAT; Infant feeding; Childhood obesity; Response rates; Questionnaire completion; Outcome measurements